A free and open-source solution for Rietveld refinement of XRD data from the CheMin instrument onboard the Mars rover Curiosity. (December 2022) - Döbelin, Nicola; Archer, Richard; Tu, Valerie
Abstract: The Rietveld refinement software Profex is an open-source and platform-independent solution for the processing of powder X-ray diffraction datasets. It is based on the BGMN refinement kernel and uses a description of the diffractometer configuration to determine the instrument-related peak profile. In this article we present a Profex configuration file for the Chemistry and Mineralogy (CheMin) X-ray diffractometer (XRD), which is on-board the Mars Science Laboratory rover Curiosity . For the past decade, Curiosity has been on a mission on Mars to find out whether the planet was once habitable for microbial life. The CheMin XRD determines the mineralogical phases and abundances of Martian soil and rocks in Gale Crater, Mars. Since its arrival on Mars in 2012, Curiosity has analyzed powdered soil and rock samples with the CheMin instrument and transmitting the raw XRD data acquired back to Earth. Adaptations of Profex to work seamlessly with CheMin XRD datasets involved creating a new configuration file for the CheMin instrument, as well as adding the Mars Mineral Compendium, a compilation of structural models specifically selected for the analysis of Mars sedimentary soil and rock samples, to Profex . Using example refinements, we demonstrate that this software solution is well suited for quantitative analysis of CheMin XRD datasets. Highlights: CheMin was sent to Mars on-board the Rover Curiosity to analyze Martian rock and soil samples by XRD. Profex is a software for the processing of XRD datasets by Rietveld refinement. We adapted Profex for the refinement of CheMin XRD datasets. Successful phase identification and quantification with Profex was demonstrated. Profex is open-source software and runs on all major operating systems.